Digital Marketing Capability, Market Orientation, and Innovation on Micro Culinary Performance: Social Capital's Moderating Role - Dhevi Dadi Kusumaningtyas; Denny Bernardus; Liliana Dewi (CV. Sakura Digital Nusantara, 2026)
Purpose – This study examines whether digital marketing capability, market orientation, and innovation raise the performance of micro culinary enterprises in Surakarta (Solo), Indonesia, and whether social capital moderates each capability-performance relationship. Design/methodology/approach – Survey data from 250 owner-managers of micro culinary enterprises were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM), Confirmatory Tetrad Analysis, and Necessary Condition Analysis (NCA). Finding/Results – Digital marketing capability, market orientation, and innovation each significantly and positively predicted performance. All four constructs, including social capital, met the threshold for a meaningful necessary condition, though digital marketing capability's bottleneck is largest only near the extreme upper tail of performance. Social capital significantly strengthened only the market orientation-performance relationship; its large direct coefficient should be read alongside its high variance-inflation factor rather than as evidence of dominance. Originality/Value – The study offers evidence that Social Capital Theory's boundary-condition role can be selective rather than uniform, based on a single significant interaction of three tested, and extends the Resource-Based View to micro-scale, informal culinary enterprises, offering a preliminary basis for sequencing capability-building support pending replication.